Green's function for tangentialy loaded horizontaly layered half-space - Pliberšek, Tomaž (Acta geotechnica Slovenica, 2008)
The topic of this paper is a novel evaluation of the integral representation of the surface Greenćs function for a layered half-space, loaded on its surface by a harmonic tangential point force. The equations of motions are reduced to wave equations by the introduction of wave potentials. The Hankel transform is applied to them and they are consecutively solved leading to the integral representation of surface displacements. They are consecutively evaluated by the proposed three step procedure. First the singularity is extracted. It is further noted that so obtained integrals, after suitably chosen branch cuts and analytic continuation of integrands are introduced, can be evaluated by contour integration for an arbitrary number of layers. They are, therefore, expressed by number of residues at the poles of integrand and the integrals along finite portions of the branch cuts. The latter ones can easily be evaluated to any desired accuracy leading to a closed form solution. Some numerical results corroborating the presented approach are given.
Keywords: elastodinamika; gradbena statika; Greenova funkcija; Hankelova integralska deformacija; horizontalna točkovna obremenitev; valovanje